A ética das virtudes e o problema do relativismo moral - Nascimento, José Rudson Fidélis do (2025)
The general objective of this work is to examine some discussions on virtues and the problem of relativism in the contemporary philosophical debate. In this sense, considering that, for moral relativism, different cultures incorporate different virtues, the purpose of this dissertation is to demonstrate how relativist ethics becomes a problem for Aristotelian virtue ethics, which seeks to offer an objective and universal foundation for human virtues. Therefore, the research aims to answer to what extent human virtues depend on objective foundations of human nature. Thus, the goal is to elucidate the arguments of some of the main neo-Aristotelian proponents of contemporary virtue ethics, such as Philippa Foot and Rosalind Hursthouse, in an attempt to respond to the problem of moral relativism. In view of this, these authors argue that it is possible to integrate morality into a naturalistic perspective, in order to demonstrate that it is grounded in the nature of human beings, and that this fact is sufficient to justify a universal and objective ethics, making clear that the exercise of virtues does not depend on contingent and subjective factors.